2017
DOI: 10.1186/s12864-017-3636-3
|View full text |Cite
|
Sign up to set email alerts
|

CNV discovery for milk composition traits in dairy cattle using whole genome resequencing

Abstract: BackgroundCopy number variations (CNVs) are important and widely distributed in the genome. CNV detection opens a new avenue for exploring genes associated with complex traits in humans, animals and plants. Herein, we present a genome-wide assessment of CNVs that are potentially associated with milk composition traits in dairy cattle.ResultsIn this study, CNVs were detected based on whole genome re-sequencing data of eight Holstein bulls from four half- and/or full-sib families, with extremely high and low est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 97 publications
4
40
0
Order By: Relevance
“…SPP1 is associated with milk protein percentage, milk yield, milk protein yield, and lactation regulation in dairy cattle [57]. Signatures of selection near the SNCA, potentially related to milk protein and fat traits in dairy cattle [58] were reported by DSMC for the Kulundin, Volgograd, Krasnoyarsk, and Baikal breeds. Two family members, the ACSS1 and ACSS2 previously associated with the mammary gland function and milk fatty acid composition in sheep [59,60], cattle [61], and yaks [62] were the top-ranked genes in positively selected regions reported by DCMS.…”
Section: Milk and Lactation-related Traitsmentioning
confidence: 97%
“…SPP1 is associated with milk protein percentage, milk yield, milk protein yield, and lactation regulation in dairy cattle [57]. Signatures of selection near the SNCA, potentially related to milk protein and fat traits in dairy cattle [58] were reported by DSMC for the Kulundin, Volgograd, Krasnoyarsk, and Baikal breeds. Two family members, the ACSS1 and ACSS2 previously associated with the mammary gland function and milk fatty acid composition in sheep [59,60], cattle [61], and yaks [62] were the top-ranked genes in positively selected regions reported by DCMS.…”
Section: Milk and Lactation-related Traitsmentioning
confidence: 97%
“…CNV is an important source of genetic variation complementary to SNP. CNV is associated with not only disease and abnormal development in livestock and poultry but also physical appearance and many economic traits [10][11][12][13]. For example, Wright [14] found that the first intron CNV of the SOX5 gene is related to crown type.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 7228 CNVRs were obtained after merging overlapping CNVs, which greatly exceeded the numbers previously reported for sheep based on SNP50 chip and SNP600 chip studies [11,13,15,16]. This difference was not surprising, as the genomic coverage of SNP chips is poor, which results in the detection of longer CNVRs [17,18]. The CNVRs detected in this study accounted for 2.17% of the sheep reference genome, which falls within the range (0.8%-5.12%) reported for horses, pigs, cattle and chickens [19][20][21][22].…”
Section: Discussionmentioning
confidence: 81%